Serum glial fibrillary acidic protein in acute stroke: feasibility to determine stroke-type, timeline and tissue-impact - Paul, Julien F.; Ducroux, Célina; Correia, Pamela; Daigneault, Audrey; Larochelle, Catherine; Stapf, Christian; Gioia, Laura C. (Frontiers in Neurology, 2024)
BackgroundInterest is emerging regarding the role of blood biomarkers in acute stroke. The aim of this pilot study was to determine the feasibility of biomarker acquisition in suspected acute stroke, using modern ultrasensitive immunoassay techniques, and explore their potential usefulness for stroke diagnosis and management.MethodsIn 62 patients with suspected acute stroke, blood samples were prospectively obtained upon arrival and prior to neuroimaging. Serum levels of glial fibrillary acidic protein (sGFAP) and neurofilament light chain (sNfL) were analyzed using a single molecule array (SIMOA®) method, according to time of symptom onset, neuroimaging, and final diagnosis.ResultsAcute ischemic stroke (AIS) was diagnosed in 35 patients, 10 with large-vessel occlusion (LVO). The remaining were diagnosed with intracerebral hemorrhage (ICH) (n = 12), transient ischemic attack (n = 4), and stroke mimics (n = 11). Median (IQR) sGFAP levels were significantly higher in ICH (2,877.8 [1,002.1–10,402.5] pg./mL) compared to others diagnoses. In AIS, GFAP levels appear to increase with longer delays since symptom onset and were higher in patients with more extensive ischemic changes on baseline CT (ASPECTS ≤7) than those without, particularly in LVO stroke. NfL values were similar across groups.ConclusionIn acute stroke, serum GFAP levels show potential as an adjunct tool for the distinction between ICH and AIS. Specific to AIS, GFAP may also offer insight into time from onset, and extent of ischemic tissue injury on neuroimaging, particularly in LVO stroke. These preliminary findings merit further study.